2014
DOI: 10.1016/j.paid.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Mindful eating: Trait and state mindfulness predict healthier eating behavior

Abstract: Obesity and excess weight are significant societal problems. Mindfulness may encourage healthier weight and eating habits. Across four studies, we found a positive relation between mindfulness and healthier eating. Trait mindfulness was associated with less impulsive eating, reduced calorie consumption, and healthier snack choices. In addition, we found a causal effect of mindfulness on healthier eating. An experimental manipulation of state mindfulness led participants to consume fewer calories in a spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
119
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(153 citation statements)
references
References 26 publications
14
119
3
6
Order By: Relevance
“…Mindful eating is the application of mindfulness fundamentals on food-related experiences; that is, purposeful attention to the present moment with a non-judgmental or accepting attitude. Mindful eating has been related to healthier eating [32], and has been suggested to drop glucose levels and assist weight loss through mindfulness-based interventions [33]. Whether or not mindful eating relates to frequency of visits to AYCEB has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Mindful eating is the application of mindfulness fundamentals on food-related experiences; that is, purposeful attention to the present moment with a non-judgmental or accepting attitude. Mindful eating has been related to healthier eating [32], and has been suggested to drop glucose levels and assist weight loss through mindfulness-based interventions [33]. Whether or not mindful eating relates to frequency of visits to AYCEB has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis from this study indicated that gender was related to mindfulness, with men statistically more mindful than women. This study was one part of a 4-part study and no gender effects were seen in the other 3 sub-studies (54). However, because of this finding and that of other studies, the effects of gender on energy intake should be taken into consideration.…”
Section: Gender Of Subjectsmentioning
confidence: 80%
“…After the intervention, participants were instructed to "eat as many M&Ms, pretzels, and almonds as you would like". Participants in the mindfulness condition ate 24% fewer calories than those in the control condition as measured by food weight (54). Results from these two sub-studies indicate that both trait mindfulness (indicative of potential "chronic" mindfulness) and a brief mindfulness based intervention were associated with decreased calorie intake.…”
Section: Mindfulnessmentioning
confidence: 87%
See 2 more Smart Citations